Pengaruh Person Job Fit dan Budaya Kerja Terhadap Organizational Citizenship Behavior Karyawan Kantor Rektorat Universitas Islam Kalimantan (Uniska) Muhammad Arsyad Al Banjari Banjarmasin - Muhammad Alfani; Muhammad Hadini (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2017)
This research assign samples are 50% of the population of 70 people or a sample of 35 respondents on Rectorat Office Islamic of Kalimantan University Muhammad Arsyad Al Banjari Banjarmasin. Methods of Data collection in the researchers used is observation, questionnaire, and documentation. Each indicator made questionnaire respectively of 3 statement. Job Fit Person variables are 8 indicator to the questionnaire as many as 24 statement, Work Culture questionnaire contained 13 indicators with a total of 39 statements, and Organizational Citizenship Behavior as many as eight indicators with a questionnaire with 24 statements. Overall there are 87 statement questionnaire. Furthermore, linear regression analysis partial and simultaneous with Statistical Programe Social Sciencies (SPSS) software version 19.0. The result found that Person job fit is not significant and does not affect to Organizational Citizenship Behavior. Further work culture significantly influence to Organizational Citizenship Behavior, and as well as simultaneously Person job fit and work culture significantly influence to Organizational Citizenship Behavior. Keyword : Person Job Fit, Work Culture, Organizational Citizenship Behavior